Mechanochemical synthesis of bismuth ferrite - Marinković-Stanojevića Z.; Mančić L.; Srećković T.; Stojanović B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A powder mixture of Bi2O3 and Fe2O3 was mechanically treated in a planetary ball mill in an air from 30 to 720 minutes. It was shown that the mechanochemical formation of BiFeO3 (BFO) phase was initiated after 60 min and its amount increased gradually with increasing milling time. A detailed XRPD structural analysis is realized by Rietveld’s structure refinement method. The resulting lattice parameters, relative phase abundances, crystallite sizes and crystal lattice microstrains were determined as a function of milling time. Microstructural analysis showed a little difference in morphology of obtained powders. The primary particles, irregular in shape and smaller than 400 nm are observed clearly, although they have assembled together to form agglomerates with varying size and morphology. Dense BFO ceramics were prepared by conventional solid-state reaction at the temperature of 810ºC for 1h followed immediately by quenching process. [Projekat Ministarstva nauke Republike Srbije, br. III45007: Zero- to Three-Dimensional Nanostructures for Application in Electronics and Renewable Energy Sources: Synthesis, Characterization and Processing